Asymptotic Behavior of Solutions of Systems of Functional Differential Equations with Nonlinear Deviation of Argument - Oleinichenko, A. P. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
For systems of functional differential equations with nonlinear deviation of argument, we obtain sufficient conditions for the existence of families of their solutions that are continuously differentiable for t ∈ R +. We also investigate the asymptotic behavior of these solutions.